Use of cefepime, meropenem, or piperacillin/tazobactam as initial treatment for febrile neutropenia in patients with hematological malignancy - a real-life experience - Najmul Karim; Alamgir Kabir; Manirul Islam; Akhil Ranjan Biswas; Mohammed Wasim; Mahbubul Alam; Nobendu Chowdhury; Mohammed Nadimul Islam; Tamanna Tabassum; Mohammad Jahid Hasan (SpringerOpen, 2022)
Abstract Background Antimicrobials like fourth-generation cephalosporins, carbapenems, or β-lactams are widely used in treatment of febrile neutropenia (FN). The present study aimed to compare the efficacy of cefepime, meropenem, and piperacillin/tazobactam as initial treatment for chemo-induced FN in patients with hematological malignancy. Methods This was an observational study conducted in the Department of Hematology of Dhaka Medical College Hospital from July 2020 to June 2021 including 99 adult FN patients with hematological malignancy who were randomized equally to three treatment arms to receive cefepime, meropenem, or piperacillin/tazobactam as an empirical antibiotic. Response to therapy was defined as improvement in symptoms (e.g., defervescence) or in laboratory values including neutrophil counts on day 3 and day 7 after the initiation of the therapy. Chi-square test and Fisher's exact test were used to compare the efficacy of the treatment regimens. Results Response rate to initial treatment with different antibiotic regimens was similar without any statistically significant difference (60.6%, 63.6%, and 51.5% on day 3 and 63.6%, 75.8%, and 66.7% on day 7 for cefepime, meropenem, and piperacillin/tazobactam, respectively, p-value > 0.05) irrespective of underlying diagnosis, the severity of neutropenia, and cause of fever. Conclusion Initial therapy with cefepime, meropenem, or piperacillin/tazobactam is safe and equally effective in chemo-induced FN in patients with hematological malignancy. This finding may be considered in clinical practice for optimum therapeutic outcomes.